2020
DOI: 10.1093/petrology/egaa077
|View full text |Cite
|
Sign up to set email alerts
|

Slow Ascent of Unusually Hot Intermediate Magmas Triggering Strombolian to Sub-Plinian Eruptions

Abstract: To assess whether magma ascent rates control the style of volcanic eruption, we have studied the petrography, geochemistry and size distribution of microlites of plagioclase and pyroxene from historical eruptions from Tongariro, Ruapehu and Ngauruhoe volcanoes located in the southern Taupo Volcanic Zone, New Zealand. The studied deposits represent glassy andesitic and dacitic tephra shards from the Mangamate, Mangatawai, Tufa Trig and the Ngauruhoe tephra formations, ranging in age from 11,000 years BP to 1996… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 156 publications
4
15
0
Order By: Relevance
“…From a volcanological perspective, fast ascending magmas are extracted from their crustal domains and extruded onto the surface in as little as tens of minutes (Lloyd et al, 2016) when melts are hot (>1000℃) and volatile rich. Short timescales of the order of hours to days have also been inferred for volatile poor arc magmas (Lormand et al, 2020). In a rapidly ascending melt, a variety of concomitant processes may alter the physiochemical state of the melt volume, including syn-eruptive mixing (e.g.…”
Section: Experimental Designmentioning
confidence: 99%
“…From a volcanological perspective, fast ascending magmas are extracted from their crustal domains and extruded onto the surface in as little as tens of minutes (Lloyd et al, 2016) when melts are hot (>1000℃) and volatile rich. Short timescales of the order of hours to days have also been inferred for volatile poor arc magmas (Lormand et al, 2020). In a rapidly ascending melt, a variety of concomitant processes may alter the physiochemical state of the melt volume, including syn-eruptive mixing (e.g.…”
Section: Experimental Designmentioning
confidence: 99%
“…High-resolution investigations of microtextures can unravel the processes occurring at shallower depth in the leadup to eruption. For instance, recent studies focusing on crystal size distribution and numerical conduit model using microlites and microcrysts (Arzilli et al 2019;Lormand et al 2020;Moschini et al 2021) have contributed to our understanding of crystallisation kinetics during magma ascent in the conduit which revealed the links between undercooling and magma ascent rates. Although studies about microphenocryst compositional changes and textures have been reported since the late 1980s (e.g.…”
Section: Crystal Texturesmentioning
confidence: 99%
“…Martel 2012), the factors controlling eruption style (e.g. Lormand et al 2020), and to get a better understanding of degassing and crustal processes (e.g. Noguchi et al 2006).…”
Section: Origin Of Microlites and Microphenocrystsmentioning
confidence: 99%
See 2 more Smart Citations